Programmable bio‐nanochip‐based cytologic testing of oral potentially malignant disorders in Fanconi anemia. (6th April 2015) - Floriano, P. N.; Abram, T; Taylor, L; Le, C; Talavera, H; Nguyen, M; Raja, R; Gillenwater, A; McDevitt, J; Vigneswaran, N
<x xml:space="preserve">Abstract</x> Fanconi anemia (FA) is caused by mutations of DNA repair genes. The risk of oral squamous cell carcinoma (OSCC) among FA patients is 800‐folds higher than in the general population. Early detection of OSCC, preferably at it precursor stage, is critical in FA patients to improve their survival. In an ongoing clinical trial, we are evaluating the effectiveness of the programmable bio‐nanochip (p‐BNC)‐based oral cytology test in diagnosing oral potentially malignant disorders (OPMD) in non‐FA patients. We used this test to compare cytomorphometric and molecular biomarkers in OSCC cell lines derived from FA and non‐FA patients to brush biopsy samples of a FA patient with OPMD and normal mucosa of healthy volunteers. Our data showed that expression patterns of molecular biomarkers were not notably different between sporadic and FA‐OSCC cell lines. The p‐BNC assay revealed significant differences in cytometric parameters and biomarker MCM2 expression between cytobrush samples of the FA patient and cytobrush samples of normal oral mucosa obtained from healthy volunteers. Microscopic examination of the FA patient's OPMD confirmed the presence of dysplasia. Our pilot data suggests that the p‐BNC brush biopsy test recognized dysplastic oral epithelial cells in a brush biopsy sample of a FA patient.